Relationship between social support, functional outcomes and health-related quality of life in working-aged adults at three months after ischemic stroke: results from the FRAILTY study - Elena Gurková; Daniela Bartoníčková; Daniel Šaňák; Šárka Šaňáková; Jana Zapletalová; Lenka Štureková (Health and Quality of Life Outcomes)
Abstract Background The relationship between social support and functional outcomes and health-related quality of life (HRQoL) after ischemic stroke (IS) remains unclear, especially in working-aged patients. Aim To assess the relationship between perceived social support, functional outcomes, post-stroke psychosocial symptoms, and HRQoL in working-aged adults three months after IS. Methods A prospective and correlational design was used. Patients of working age (18–65 years) admitted for first-ever IS were enrolled in the prospective FRAILTY (Factors Affecting the Quality of Life After Ischemic Stroke in Young Adults) study (NCT04839887). HRQoL (using the Stroke Impact Scale, Quality of Life in Neurological Disorders), social support (using the Multidimensional Scale of Perceived Social Support), functional outcomes (using a modified Rankin Scale—mRS), and post-stroke psychosocial symptoms were assessed three months after IS. Descriptive statistics, Wilcoxon signed-rank test, Spearman’s correlations and multiple linear regression were used for analysis. Results A total of 121 (54.5% males, mean age 51.7 ± 8.4 years) IS patients were analyzed. Of those, 87.7% had excellent clinical outcomes (mRS 0–1) after three months. Patients reported significant improvement in all domains of self-reported HRQoL except memory and communication after three months. The overall perceived social support was not associated with HRQoL domains. Post-stroke depression was negatively associated with all domains of HRQoL. Living arrangements (living alone) and post-stroke depression were negatively associated with perceived social support after IS. Conclusions More insight into the relationship between variables of HRQoL in working-aged adults might increase their social participation, strengthen supportive relationships, and promote their recovery and rehabilitation process. Focusing on the management of emotional problems and supporting functional outcomes may be modifiable factors that may represent targets for strategies to improve the HRQoL. Further research is needed to clarify the relationship between pre-stroke perceived social support and its types and post-stroke psychosocial symptoms in the long term.